INTERPROFESSIONAL SPIRITUAL CARE TRAINING FOR GERIATRIC CARE PROVIDERS. (16th November 2018) - Bandini, J; Thiel, M; Meyer, E; Paasche-Orlow, S; Zhang, Q; Cadge, W
Abstract: Religion and spirituality have been shown to provide older patients and their families with a source of strength, hope, coping, and a sense of meaning in their life (Koenig et al. 1997; Krause et al. 2003). Despite the importance patients place in religion and spirituality, many patients with advanced diseases report that their religious and spiritual needs are not met by their health care team, and many non-chaplain clinicians feel unprepared to address religious and spiritual issues in their clinical practice (Balboni et al. 2013; Puchalski 2012). The purpose of this study was to assess the efficacy of a one-day workshop on spiritual care for non-chaplain clinicians who provide care elderly long-term care patients. Clinician participants (N=68) were given a pre-survey at the beginning of the workshop, a post-survey at the conclusion of the workshop, and a three month follow-up survey to evaluate their comfort in engaging in spiritual issues with patients and families before and after the workshop. Overall scores for clinicians' self-reported perceived ability and comfort in engaging in issues around spirituality with patients and their families increased significantly right after the training and after three months, although this improvement slightly diminished after three months compared to at the end of the day of the spiritual generalist workshop. This study suggests that a spiritual care training program targeted towards geriatric clinicians has the potential to provide clinicians with the tools, skills, and support they need to approach basic spiritual care with their patients and family members.